Installation for the research of galvanomagnetic effects in manganites of lanthanides - Ermaganbetov, K.T.; Chirkova, L.V.; Kassenov, B.K.; Kabiden, R.; Makhanov, K.M.; Zeinidenov, A.K.; Arinova, E.T. (KSU Publ., 2018)
In the problem of increase in volume and information processing rate removed from hard drives of computers, the large role is played by properties of the sensors used for these purposes. The modern magnetoresistive sensors not fully meet qualifying standards that constrains development of the computer equipment. Effects of colossal and gigantic magnetoresistance found rather recently (CMC and HMS) give the chance to create more perfect sensors capable to work in case of indoor temperatures and in the field of feeble magnetic fields. From the point of view of technical applications use of effect of CMC is not just enhancement of already existing computer and semiconductor technologies. It is creation of essentially new elements of operational computer memory which use will lead to essential lowering of energy consumption and increase in non-volatility not only computers, but also such devices as cell phones, electronic organizers, digital cameras and so forth. The task of fundamental physics - to understand the nature of reduction of a resistance under the influence of a magnetic field, that is origins of CMC. In this regard the problem of search and creation of the materials having effects of enormous and huge magnetoresistance, sensors of weak magnetic fields, suitable for creation, is very relevant. The manganites of lanthanides having complex structure can be examples of such materials. Anomalies of physical properties of manganites which can be used for creation of similar sensors are caused by a rich variety of the physical phenomena inherent in manganites of rare-earth elements with a perovskite structure La1-x(Sr, Ca)xMnO3. However, effective practical application of manganites requires understanding of the physical mechanisms responsible for the observed phenomena. The research of galvano-magnetic effects plays a defining role in search of new materials as they allow to receive data on fundamental properties of semiconductors. These experiments allow to determine those parameters of new materials which are the main criteria of a possibility of their use for creation of these or those sensors and sensors. The description of the experimental installation for a study of magnetic-field dependencies of kinetic coefficients, their measurements, determination of the main characteristics of materials is provided in operation.
Лантаноидтар манганиттеріндегі гальваномагниттік құбылыстарды зерттеуге арналған құрылғы
Установка для исследования гальваномагнитных эффектов в манганитах лантаноидов
Keywords: installation; magnetic semiconductors; colossal magnetoresistance; colossal magnetoresistance; sensors; ferromagnetic structures; ferromagnetic structures; electromagnet; power supply; Hall effect; manganite’s of lanthanides; register; temperature; photo compensation amplifier; DC potentiometers; control units